The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00417-015-3039-6
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vessel oxygen saturation and vessel diameter in retinitis pigmentosa at various ages

Abstract: The shifting characteristics of retinal vessel oxygen saturation suggest that the pathological mechanism of retinal oxygen metabolic disorder differs by age in patients with RP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 42 publications
5
37
0
2
Order By: Relevance
“…However, the fact that there was no significant difference between the peripapillary oxygen saturation in the UT vessels in the disc centred image and the saturation proximally from branches on the same vessels in images centred on the vascular arcades supports that illumination had not been a biasing factor for the calculation of saturation values. It has been shown that the calculation of saturation becomes unpredictable in thin and short vessel segments,20 and therefore, only vessels with a diameter larger than six pixels, with a diameter of at least 50% of their parent vessel, and vessel segments longer than 50 pixels were considered 13. It is unlikely that the conclusions of the study had been influenced by the selection of fundus images with this specific branching pattern.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that there was no significant difference between the peripapillary oxygen saturation in the UT vessels in the disc centred image and the saturation proximally from branches on the same vessels in images centred on the vascular arcades supports that illumination had not been a biasing factor for the calculation of saturation values. It has been shown that the calculation of saturation becomes unpredictable in thin and short vessel segments,20 and therefore, only vessels with a diameter larger than six pixels, with a diameter of at least 50% of their parent vessel, and vessel segments longer than 50 pixels were considered 13. It is unlikely that the conclusions of the study had been influenced by the selection of fundus images with this specific branching pattern.…”
Section: Discussionmentioning
confidence: 99%
“…; Zong et al. ). Within the RP group, strong correlations between the retinal metabolic demand and the structural (Türksever et al.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have found reduced oxygen saturation values in occluded arteries and veins [1417] and increased venous oxygen saturation in patients with exudative age-related macular degeneration (AMD) [18], advanced primary open-angle glaucoma [1921], diabetic retinopathy[2224], and retinitis pigmentosa [25, 26]. For patients with retinitis pigmentosa, increased arterial oxygenation saturation and increased arteriovenous oxygen saturation differences have been observed, with age seemingly affecting these values [27, 28]. Another study on primary open-angle glaucoma [29] indicated no change in venous oxygen saturation.…”
Section: Introductionmentioning
confidence: 99%